New considerations on the phylogeny of cyrtophorian ciliates (Protozoa, Ciliophora): expanded sampling to understand their evolutionary relationships. (7th December 2015) - Chen, Xiao; Pan, Hongbo; Huang, Jie; Warren, Alan; Al‐Farraj, Saleh A.; Gao, Shan
Abstract : To rationalize the confusing relationships among the cyrtophorian ciliates, we expanded the taxon sampling by sequencing the small subunit ribosomal RNA (SSU rRNA) gene of representatives of 12 genera (20 species, 23 new sequences). The SSU rRNA sequences of Spirodysteria, Agnathodysteria, Brooklynella and Odontochlamys are reported for the first time. Phylogenetic trees were constructed, and secondary structures of variable region 4 (V4) of all genera for which SSU rRNA gene sequence data are available were predicted. The results indicate that (i) Brooklynella is likely an intermediate taxon between Dysteriidae and Hartmannulidae; (ii) the genus Dysteria is paraphyletic with Spirodysteria and Mirodysteria nested within it; (iii) the genus Agnathodysteria is well separated from Dysteria based on both molecular and morphological data; and (iv) Trithigmostoma is a basal genus of Chilodonellidae, based on both the morphological and molecular data.